A Quantitative Study Investigating The Effect of DAFNE On The Quality Of Life (QOL) And HbA1c Of Adults With Type 1 Diabetes Mellitus (T1DM) - Jeyes, Luke (2008)
This study aimed to explore the impact of the DAFNE (Dosage Adjustment For Normal Eating) education programme upon the QOL (Quality Of Life) and HBA1c of T1DM (Type 1 Diabetes Mellitus) patients.